How Supportive and Competitive Work Environments Influence Job Attitudes and Performance in French Sales Roles - Tz-Li Wang; Wong Oscar (Yayasan Ghalih Pelopor Pendidikan, 2024)
This study explores the relationship between Supportive Psychological Climate (SPC), Competitive Psychological Climate (CPC), Job Attitude (JA), and Job Performance (JP) among sales employees in the French fashion industry. Using a sample of 259 respondents, this research investigates the direct effects of both SPC and CPC on JA and JP, while also examining the mediating role of JA between these psychological climates and performance outcomes. The findings reveal that SPC positively influences both JA and JP, while CPC does not significantly impact either variable. Furthermore, JA mediates the relationship between SPC and JP, but no such mediation is observed for CPC. These results highlight the importance of creating a supportive work environment to foster positive employee attitudes and improve performance. This study contributes to the growing literature on organizational climate by demonstrating how different types of psychological climates influence key job outcomes in a highly competitive industry.